Case report: Primary ovarian Burkitt's lymphoma: A puzzling scenario in pediatric population - Persano, Giorgio; Crocoli, Alessandro; Martucci, Cristina; Vinti, Luciana; Cassanelli, Giulia; Stracuzzi, Alessandra; Cardoni, Antonello; Inserra, Alessandro (Frontiers in Pediatrics, 2023)
Burkitt's lymphoma (BL) is defined as a highly invasive B-cell lymphoma, usually characterized by an excellent prognosis, more than 90% of children and adolescents being cured with highly dose-intensive multiagent chemotherapy. Primary ovarian localization without involvement of other organs is a rare manifestation of BL, especially in pediatric population. Symptoms at diagnosis are similar to other ovarian lesions and differential diagnosis may be challenging for clinicians. A 12-year-old girl was referred to our institution for abdominal pain and palpable mass observed by the pediatrician. Diagnostic work-up demonstrated a large mass arising from the right ovary, causing compression on abdominal aorta, inferior vena cava, ureters and bowel, with a second smaller lesion on the left ovary. At surgery, a 15 cm-large, ruptured mass arising from the right ovary was found, associated with a second lesion originating from the left ovary (8 cm) and multiple nodules of the greater omentum. Right salpingo-oophorectomy was performed, incisional biopsies were taken from the left ovary and omental nodules and peritoneal fluid samples were collected for cytology. Pathology revealed a Burkitt lymphoma and the patient underwent chemotherapy according to AIEOP LNH-97 Protocol, group R3 with Rituximab. Preoperative diagnosis of primary ovarian lymphoma is extremely difficult. Surgical exploration is often necessary in patients presenting with acute abdominal or pelvic pain; when the suspicion of primary ovarian lymphoma arises intraoperatively, every effort should be made to minimize invasive procedure in order to enhance post-operative recovery.